2001
DOI: 10.2139/ssrn.292139
|View full text |Cite
|
Sign up to set email alerts
|

Investor Sentiment and Asset Valuation

Abstract: Using the Chinese stock market data as sample, this paper investigates the impact of investor sentiment on the assets valuation. In order to classify stocks objectively, our sample stocks are sorted by double indicators (B/M and PE). In the portfolio, we find stocks with low B/M and high PE are sensitive to investor sentiment, which are considered to be costly to arbitrage. Investor sentiment has incremental power to explain stock return co-movements, which indicates that these stocks would perform higher (low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
349
5
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(394 citation statements)
references
References 40 publications
34
349
5
6
Order By: Relevance
“…Their evidence suggests that sentiment effect is limited to small firm returns and returns exert mush stronger influence on sentiment indicators. However, in their follow up research [8], they establish that the lack of effect predictability of sentiment in the short run does not prevent it from affecting asset values in the long run. They show that high sentiment is followed by low cumulative long run returns as asset prices revert to their fundamental value.…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…Their evidence suggests that sentiment effect is limited to small firm returns and returns exert mush stronger influence on sentiment indicators. However, in their follow up research [8], they establish that the lack of effect predictability of sentiment in the short run does not prevent it from affecting asset values in the long run. They show that high sentiment is followed by low cumulative long run returns as asset prices revert to their fundamental value.…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…The results of Brown and Cliff (2005) showed that in large companies or companies with a low book-to-market ratio sentiment was significant in predicting future returns in 1, 2 and 3-year time horizons. However, small stocks seem to be less influenced by sentiment.…”
Section: Behavioural Effectsmentioning
confidence: 99%
“…Although there is not a consensus on the influence of investor sentiment in stock markets, several studies have documented that sentiment influences returns and valuation of assets [Fisher and Statman (2000), Brown and Cliff (2005), Wurgler (2006, 2007), Lemmon and Portniaguina (2006), Schmeling (2009)], volatility [Wang, Keswani and Taylor (2006)], the practices of information disclosure and market reaction to announcements [Bergman and Roychowdhury (2008), Mian and Sankaraguruswamy (2008)]. Fisher and Statman (2000) analyzed the relationship between sentiment and future returns as well as the relationship between changes in sentiment and future returns.…”
Section: Behavioural Effectsmentioning
confidence: 99%
See 2 more Smart Citations